PENGARUH KONEKSI POLITIK TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Pertambangan yang terdaftar di BEI tahun 2014-2018) - Fajriatul Azizah; Muhammad Al Amin (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2020)
The company's financial condition can be described by  the company's performance which is analyzed by various financial analysis measurement tools. The financial analysis is used  to evaluate the company's financial condition as reflected by the company's performance in a period. The purpose of this study is to analyze the effect of political connections on company performance, especially in mining companies. Tobin's q is used as an indicator to measure company performance. This research use data from annual report  of mining sector companies listed on the Stock Exchange Indonesia in 2014-2018, which total 75 companies. Data collection method by purposive sampling method in order to get  representative sample criteria Hypothesis testing uses multiple linear regression analysis. The results of the study that political connections do not affect the company's performance, as measured by the proportion of independent directors who have political connections.